1998
DOI: 10.1055/s-2007-993945
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Sporadic Deceleration During Antepartum Testing in Term Pregnancies

Abstract: We have investigated the significance of single sporadic deceleration during reactive nonstress testing in normal pregnancies at term. A prospective study was performed during a 1-year period including 4742 nonstress tests performed between the 38th and 42nd weeks of pregnancy in patients referred to our department for antepartum testing and without any complication or pathology. Nonstress test (NST) was carried out with the patient lying on her left side, and was defined as reactive if at least two accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…Most SSDs are most likely variable decelerations, that are caused by temporary cord compression [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most SSDs are most likely variable decelerations, that are caused by temporary cord compression [9].…”
Section: Discussionmentioning
confidence: 99%
“…Variable decelerations are common during fetal heart rate monitoring and may be seen in up to 50% of NSTs [8]. The evidence regarding the clinical signi cance of a single sporadic variable deceleration (SSD) during fetal heart rate tracing during reactive NST is scarce, and previous studies have yielded con icting results [8, [9][10][11][12][13][14][15]. Therefore, the optimal management of SSD during NST for a fetus without other signs of fetal compromise has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…2 The incidence of non-reassuring fetal conditions during labor is significantly higher in these fetuses with sporadic decelerations when compared to the normal parturient population. 1,2 Moreover, major, sporadic FHR decelerations may also be associated with relatively trivial behavioral changes in physiologically normal human fetuses. 3 Additional studies in fetal humans 4-6 and sheep 7,8 have found that vibroacoustic stimulation can alter fetal behavioral states associated with benign FHR decelerations.…”
Section: Introductionmentioning
confidence: 98%
“…In human fetuses, the occurrence of a single sporadic deceleration at gestational ages of 32–42 weeks is not an alarming sign, providing the non‐stress test (NST) and/or contraction stress test (CST) are reassuring 1 . However, the presence of repeated sporadic decelerations during a reactive NST suggests that cord compromise is persistent and recurrent cord compression can occur 2 . The incidence of non‐reassuring fetal conditions during labor is significantly higher in these fetuses with sporadic decelerations when compared to the normal parturient population 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation